2013
DOI: 10.1007/s11357-013-9596-x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-training-induced changes in metabolic capacity with age: the role of central cardiovascular plasticity

Abstract: Although aging is typically associated with a decline in maximal oxygen consumption (VO 2max ), young and old subjects, of similar initial muscle metabolic capacity, increased quadriceps VO 2max equally when this small muscle mass was trained in isolation. As it is unclear if this preserved exercise-induced plasticity with age is still evident with centrally challenging whole body exercise, we assessed maximal exercise responses in 13 young (24±2 years) and 13 old (60± 3 years) males, matched for cycling VO 2m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 51 publications
8
46
1
2
Order By: Relevance
“…Peak VO 2 /HR strongly correlates with peak stroke volume, and therefore, it is considered an index of SV. Moreover, it was previously reported that peak AVO 2 diff did not change after exercise training in either the young or in older adults . Based on the Fick principle and this previous report, our results suggest that a reduction in SMI is one of the most important factors affecting the deterioration of peak SV.…”
Section: Discussionsupporting
confidence: 78%
“…Peak VO 2 /HR strongly correlates with peak stroke volume, and therefore, it is considered an index of SV. Moreover, it was previously reported that peak AVO 2 diff did not change after exercise training in either the young or in older adults . Based on the Fick principle and this previous report, our results suggest that a reduction in SMI is one of the most important factors affecting the deterioration of peak SV.…”
Section: Discussionsupporting
confidence: 78%
“…Of note, fractional shortening was different between groups throughout the lifespan (ATFL/CFL and SHAMSED vs. CFL and SHAM) primarily due to alterations to LV EDD. The greater LV EDD and FS of these mice are most likely the result of the greater exercise activities of these mice, resulting in the common central cardiovascular response of volume-overload hypertrophy to regular aerobic exercise (Ehsani et al 2003;Rodeheffer et al 1984;Seals et al 1994;Wang et al 2014). Thus, FS and LV EDD were increased in these mice, through the use of the Frank-Starling effect, suggestive of a greater stroke volume.…”
Section: Discussionmentioning
confidence: 95%
“…Although encouragement was given to the patients to continue their test to exhaustion, psychological factors may certainly explain their ~10% lower HR peak compared to the healthy references. However, it is possible that their untrained status may have led to a physiological impairment and lower HR peak , as observed with, for example, advancing age . Moreover, it could also be explained by the use of second‐generation antipsychotics, such as clozapine, which increases adrenergic activity and heart rate during rest and may cause autonomous dysregulation .…”
Section: Discussionmentioning
confidence: 99%